Sociedades Quilombolas na Amazónia Brasileira – Terra e Liberdade - Funes, Euripedes (Trabalhos de Antropologia e Etnologia, 2020)
Quilombola societies of the Trombetas River, in the western state of Pará – Brazilian Amazon, were formed during the XIX century. Nowadays materialized in the current black communities – descendants of these mocambos – the struggle that arises, rather than freedom, is for the right to land, to guarantee that territoriality constituted by their ancestors, facing the large mining projects, the construction of dams, the agribusiness and even environmental projects, advocated by the federal government since the 1970s, ignoring the rights and cultures of these Afro-Amazonians. Moments in which their identity is affirmed.